The effect of glutathione on 2‐hydroxyethylmethacrylate cytotoxicity and on resin–dentine bond strength. (9th November 2013) - Nassar, M.; Hiraishi, N.; Islam, M. S.; Tamura, Y.; Otsuki, M.; Kasugai, S.; Ohya, K.; Tagami, J.; Tay, F. R.
Abstract Aim To evaluate the influence of reduced glutathione (GSH) application on 2‐hydroxyethylmethacrylate (HEMA) cytotoxicity on rat pulpal cells and evaluate the effect of etched‐dentine treatment with GSH on the immediate microtensile bond strength (μTBS) of etch‐and‐rinse adhesive. Methodology The cytotoxicity of 10 mmol L−1 HEMA, 10 mmol L−1 HEMA + 1 mmol L−1 GSH, 10 mmol L−1 HEMA + 5 mmol L−1 GSH and 10 mmol L−1 HEMA + 10 mmol L−1 GSH was compared (6 h and 24 h). Cells viability was measured by means of 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay, followed by morphological observation of cells. Etched‐dentine surfaces were rinsed and treated with one of the following solutions: 2% GSH, 5% GSH or 10% GSH, bonded with Adper Single Bond Plus (3M, ESPE, St. Paul, MN, USA) and restored with resin composite. The control group received no GSH treatment. After 1 day of water‐storage at 37 °C, the specimens were subjected to μTBS testing. Cytotoxicity and μTBS data were analysed by one‐way anova and Tukey post hoc tests (P < 0.05). Results There were significant differences between the groups. HEMA elicited a remarkable toxic effect. 10 mmol L−1 GSH prevented HEMA‐induced damage at both exposure times. Whilst 5 mmol L−1 GSH lost its protective effect at 24‐h exposure time and 1 mmol L−1 GSH showed no protective effect at both exposure times, GSH had no significant effect on the immediate μTBS; however, 5% GSH had higher bond strength value when compared to 10% GSH (P = 0.003). Conclusion Controlled concentrations of GSH had a protective effect against HEMA cytotoxicity. GSH had neither positive nor negative influence on μTBS.